PSYCHOLOGICAL SUPPORT TO CANCER PATIENTS - ZOIROVA DODAR JUMAQUL QIZI; NURALIYEVA MARJONA MANSUROVNA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
If you need help, there are teams of experts available who understand how cancer affects a person and their loved ones. It is normal to need some extra help when you’re dealing with cancer. In fact, studies show that people with cancer who have social and resource support report better quality of life. But many people who could benefit from support services don't use them because they don’t know about them or don’t know how to find them. Some people have more specific mood changes, such as anxiety, depression and distress.